2022
DOI: 10.3390/molecules27196467
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of Plant/Macrofungi/Algae-Derived Non-Starch Polysaccharide in Colitis Curing: Review of Possible Mechanisms of Action

Abstract: Multiple in vitro and in vivo model investigations have suggested a broad spectrum of potential mechanisms by which plant/macrofungi-derived non-starch polysaccharides may play a role in the treatment of inflammatory bowel disease (IBD). This article reviews the in vivo and in vitro evidence of different plant-derived polysaccharides for IBD therapy. Their underlying mechanisms, particularly the molecular mechanisms associated with protective effects in the treatment and prevention of IDB, have been well summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…An increasing number of studies have shown that polysaccharides have wide range of pharmacological effects, especially the protective effects on gastrointestinal ora [22][23][24][25]. Polysaccharides extracted from the sporoderm-broken spores of Ganoderma lucidum (BSGLP) show suppression effects of obesity and in ammation through modulating in ammation, gut microbiota, and gut barrier function [26].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that polysaccharides have wide range of pharmacological effects, especially the protective effects on gastrointestinal ora [22][23][24][25]. Polysaccharides extracted from the sporoderm-broken spores of Ganoderma lucidum (BSGLP) show suppression effects of obesity and in ammation through modulating in ammation, gut microbiota, and gut barrier function [26].…”
Section: Introductionmentioning
confidence: 99%